Home-work: a study of home at the threshold of autoethnography and art practice - Oskay Malicki, Harika Esra (The University of Edinburgh, 2014)
The movement of people and the fluxes of the world create complex topographies and destabilise the location of our homes. In this practice-based PhD, I explore the shifting sense of home that this manifests. The dramatic transformation of the boundaries of home that demarcates the borders between ‘here’ and ‘there’, “us” and ‘them’ is examined through an autoethnographically informed approach, which takes the researcher’s self as a medium as well as a source of research. Based on personal experience, the changing nature of ‘home’ is studied as it is anchored into the self, adopting an approach that studies the cultural through the personal. In this research, the methods of research are: strategies of observing, attending to the unsettling forces of the unfamiliar, documenting my personal responses on a daily basis, and unpacking some of the existing forms and practices that sustain ideas of belonging and proposing new forms of expression to this unhomely feeling. In this study, the objective is the study of the field (including the dissolving of the ground one is standing on) and the proposing new forms, new visions. This being the case, my methods come from the disciplines of autoethnography and art practice. Throughout my PhD, I aimed to negotiate the different means these two approaches work through their field that challenges the issues of representation, documentation and presentation in cultural inquiry. This thesis explores the transformation of the sense of home and my own sense of belonging based on personal experience. It is also a contribution to the discourse that has flourished between ethnography and contemporary art over the last two decades. The project is situated at the transdisciplinary site between artistic and ethnographic disciplines and reconsiders their mutual interest in the work of cultural inquiry. With a particular focus on the moment that inquiry meets its public, I explored other possibilities of “graphy” (writing) that conventionally translates as a descriptive, textual representation in ethnography. I strived to suggest alternative forms through the ways artistic inquiry work on its field that takes this moment of encounter as a crucial part of its process. Thus, the thesis is an account of these negotiations that complements the experiments in my art practice, through which I have explored the dialogue between the two distinctive approaches to inquiry.
Keywords: autoethnography; home; ethnographic turn in contemporary art